Lecture on the Positive and Negative Impact of the Internet for School-Age Children in Laucimba Village, Karo District - Pelista Br Karo Sekali; Wisno Saputra Sembiring; Pepy Pebyola Br Tarigan; Emila Sari Br Milala; Astri Lovianika Br Ginting (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this community service project is to raise awareness of the benefits and drawbacks of the Internet for school-age children in Laucimba Village, Kabanjahe District, Karo Regency, among parents and young people. This socialization process follows a multi-stage method: The PGSD Lecturer/Lecturer team hosts orientation sessions for village heads and parents. They also deliver lectures on the benefits and drawbacks of internet use for school-age children, oversee program monitoring and evaluation, and compile activity reports. It is anticipated that this pastime will force parents to stay with their kids when they browse the internet at home. Instill responsible online conduct to kids. Parents and students are aware of the different risks involved in connecting online with strangers